Examining the relationship between commercial and residential land uses and energy consumption using Gis and Vickor model (case study: District 6) - Rezaei, Mojgan; Ranjbar, Mohsen; Azadbakht, Bahram; Estelaji, Alireza (Nexo Revista Científica, 2021)
The city is a living thing whose population determines its future. Given its administrative and political pole in Iran, Tehran has attracted a significant population and District 6, given the establishment of commercial-administrative centers is the administrative pole. The purpose of the study was to examine and compare the energy consumption in the field of transportation and administrative-commercial buildings. For this purpose, the research method was based on a researcher-made questionnaire based on 6 main variables and 49 items. The sample size of 384 people was selected to reach the results using Cochran's test to answer. The study was applied in terms of purpose and descriptive-analytical in terms of nature. Data collection was based on library documents, and Vikor test was used to rank energy consumption and reach the final results. It has to be acknowledged that the results showed a significant relationship between social and economic factors in the field of transportation and residential and commercial areas until the end of January 2019. Other cases followed a 5-year pattern with a not-so-low consumption rate. Moreover, there was a significant relationship between pollutant production and energy consumption in the second quarter of each year. The statistical results based on the Vickor model showed that the first and second conditions of the above statistical test were confirmed and Districts 2, 3 and 8 have the best rank in terms of Q value, respectively, and the final result is correct.